2020
DOI: 10.7759/cureus.9326
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Lemierre’s Syndrome With a Focus on Ophthalmologic Complications

Abstract: Lemierre's syndrome (LS), once known as "the forgotten disease," is a rare and potentially lifethreatening condition that has had a gain in incidence over the last 30 years due to a variety of factors that could include changes in antibody prescription patterns, particularly in regard to the treatment of pharyngitis/tonsillitis. Due to its low incidence and broad spectrum of symptoms, LS does not have an obvious clinical diagnosis and can confuse the clinician managing the patient. Furthermore, it is equally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 43 publications
(144 reference statements)
0
36
0
3
Order By: Relevance
“…As a comparison, the previously mentioned 2016 review by Johannesen and Bodtger identified 137 LS patients over only five years (2010-2015), and they had a very similar inclusion criterion as we did [3]. Our 2020 review found that impaired extraocular motility, which would present as diplopia and cranial nerve III, IV, and VI palsies, was the most common presenting symptom, with 88.89% of LS cases (24 cases) presenting with that ophthalmological complication: abducens nerve palsies specifically occurred in 50% of LS cases (12 cases) with extraocular motility impairment and 44.44% of all LS cases with ophthalmological complications as defined by that criteria [20]. Our patient in this case had many symptoms that would classify her as having LS with ophthalmological complications including diplopia, bilateral abducens nerve palsies, blurred vision, and proptosis.…”
Section: Study (Year)mentioning
confidence: 72%
See 4 more Smart Citations
“…As a comparison, the previously mentioned 2016 review by Johannesen and Bodtger identified 137 LS patients over only five years (2010-2015), and they had a very similar inclusion criterion as we did [3]. Our 2020 review found that impaired extraocular motility, which would present as diplopia and cranial nerve III, IV, and VI palsies, was the most common presenting symptom, with 88.89% of LS cases (24 cases) presenting with that ophthalmological complication: abducens nerve palsies specifically occurred in 50% of LS cases (12 cases) with extraocular motility impairment and 44.44% of all LS cases with ophthalmological complications as defined by that criteria [20]. Our patient in this case had many symptoms that would classify her as having LS with ophthalmological complications including diplopia, bilateral abducens nerve palsies, blurred vision, and proptosis.…”
Section: Study (Year)mentioning
confidence: 72%
“…Blurred vision or decreased visual acuity was specifically one of her earliest presenting symptoms along with diplopia. She also specifically had cavernous sinus thrombosis, which occurred in 70.37% (19 cases) of cases in our systematic review, and decreased visual acuity, which occurred in 29.63% (8 cases) of those cases [20]. The majority of cases in our review had imaging that confirmed IJV thrombosis (81.48%; 22 cases) but did not have culture confirming F. necrophorum from a sterile site (only 33.33%; 9 cases) [20].…”
Section: Study (Year)mentioning
confidence: 86%
See 3 more Smart Citations